Impact of Physical Activity on All-Cause Mortality According to Specific Cardiovascular Disease - Kim, Moon-Hyun; Sung, Jung-Hoon; Jin, Moo-Nyun; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Pak, Hui-Nam; Lee, Moon-Hyoung; Lip, Gregory Y. H.; Yang, Pil-Sung; Joung, Boyoung (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with cardiovascular disease (CVD) tend to have higher mortality rates and reduced physical activity (PA). We aimed to evaluate the effect of PA on mortality in older adults with specific CVD. Methods: We enrolled 68,223 participants (n=23,871 with CVD, n=44,352 without CVD) aged ≥65 years with available physical activity data between 2005 and 2012 from the Korean National Health Insurance Service of Korea-Senior database. CVD was defined as a history of ischemic stroke, transient ischemic attack, heart failure, myocardial infarction, and peripheral artery disease. Results: Patients with CVD were older than those without CVD. Compared with the sedentary group, the physically active groups with and without CVD had a lower incidence and risk of all-cause death during a median follow up period of 42 (interquartile range 30-51) months. A 500 metabolic equivalent task-min/week increase in PA resulted in an 11% and 16% reduction in the risk of mortality in the non-CVD and CVD groups, respectively. With regard to specific CVDs, the risk of mortality progressively reduced with increasing PA in patients with heart failure or myocardial infarction. However, the reduction reached a plateau in patients with stroke or peripheral artery disease, but was significantly greater in patients with stroke (20% vs without stoke, 11%, Pint=0.006) or heart failure (13% vs without heart failure, 11%; Pint=0.045) Conclusions: PA was associated with a reduced risk of all-cause mortality in older adults with and without CVD. The benefits of PA in patients with CVD, especially patients with stroke or heart failure, were greater than those without.